KEGIATAN PENGABDIAN KEPADA MASYARAKAT : Perancangan Sarana Pendidikan Anak Usia Dini Untuk Sekolah Cahaya Al-fuqron, Desa Gunung Sari, Kecamatan Mauk, Kabupaten Tanggerang - Devanny Gumulya; Ryan Adiputra (Jurnal Dimensi Seni Rupa dan Desain, 2018)
Abstract Early childhood education is one of the most important stages in the process of child growth. This program was designed in order to prepare young children for further education at the elementary school stage. However, many early childhood education facilities, especialy owned by the government located in villages still have unfeasible facilities, based on data from Early Childhood Education Association in 2016. From unfit buildings to inadequate learning facilities. UPH saw this as an oppounity to do community service, since it is necessary to design an appropriate and suitable learning tool for children in their early childhood age, in which case study was conduct on an early childhood education facility located in a village in Mauk area, Cahaya Al Fuqron. The design process begins with researching data through observation to the facility, interviews with the people in the area as well expert on the early childhood education. The results were twenty multifunction furnitures designed and produced for the school. Hopefully in the long run this can be developed to another inadequate early childhood education facilities in other villages and provide appropriate and suitable facilities to the children with lower-middle class target market. The design also supports the home-based furniture industry and as an effort to support and assisting early childhood education nationally.